Pink Shoes Business Practices - Hermawan, Anggi (Journal of Comprehensive Science, 2023)
Shoes are one of the important needs for all ages where wearing shoes can directly support the performance of our appearance. purchasing decisions including fashion. At present, changes in people's lifestyles are influenced by fashion and this is what makes the industry movement in the fashion sector more consumptive. In the world of fashion, changes for the sake of changes in style occur continuously like shoe models. The city of Kebumen is one of the places that has a great opportunity to build an imported shoe business because shoe stores that sell imported shoes with quality brands are still rare and not many can be found. So the purpose of this study is to find out the implementation of the PinkShoes shoe company strategy, in maintaining business and solving existing problems from a marketing perspective. In this study the authors used the approach of segmentation, targeting, and positioning. The result of the research is a comparison between the strategic plan and the running of the business. It can be concluded that Pinkshoes in the implementation of business activities is always carried out according to plan, but for results there is still something that needs to be done for adjustments and improvements so that they can compete with others. In implementing Pinkshoes' business activities, it experienced several problems. From the practices that have been carried out by the Pink Shoes shoe business, there has been a change in strategy. This is due to the impact of the Covid 19 pandemic. So this also has an impact on estimated financial statements. Because the changes made adjust to the circumstances and the right strategy so that you don't experience significant losses.